0178 The Short-Lived Benefit Of Caffeine On Positive Mood During Chronic Sleep Restriction. (12th April 2019) - Doty, Tracy Jill; Mantua, Janna; Alger, Sara E; Ratcliffe, Ruthie H; So, Christine J; Balkin, Thomas J; Capaldi, Vincent F
Abstract: Introduction: While caffeine has been shown to slow the decline of self-reported positive mood compared to placebo during total sleep deprivation, what happens during chronic sleep restriction is not well known. Additionally, the effect of caffeine on mood beyond two nights of sleep restriction has not been studied. The current study aimed to investigate the impact of caffeine on positive mood (i.e., happiness) during chronic sleep restriction using a simulated work week design [e.g. 5 nights of 5 hours time-in-bed (TIB)]. Methods: Forty-eight healthy subjects underwent 5 nights of sleep restriction (TIB: 5 hr/night), followed by 3 nights of recovery sleep (TIB: 8 hr/night) in a sleep laboratory. Caffeine gum (200 mg) or placebo was administered at 0800 and 1200 hrs each day during the sleep restriction phase. While awake subjects rated hourly how well six happiness words described their current state. Results: There was a strong main effect of day, such that both groups reported decreasing happiness throughout sleep restriction [p=5.78 x 10 -8 ] and recovery [p=4.54 x 10 -9 ] compared to baseline. There was an increase in happiness on the final day of recovery for both groups, but neither group fully recovered back to baseline levels. Interestingly, there was an interaction between day and group during sleep restriction [p=0.04] such that participants receiving caffeine reported higher levels of happiness than those receiving placebo after the first night of sleep restriction. However, no subsequent group differences were seen during the rest of sleep restriction or into recovery. Conclusion: Unsurprisingly, all participants reported decreased happiness during chronic sleep restriction. However, caffeine slowed the decline of self-reported happiness compared to placebo following the first night of sleep restriction. Nonetheless, the effect was lost after the following night of sleep restriction and the groups continued to be indistinguishable throughout the rest of the experiment. These results indicate that caffeine's ability to prevent a decrease in positive mood is limited during chronic sleep restriction. Support (If Any): Department of Defense Military Operational Medicine Research Program (MOMRP)